Differences in neural and cognitive response to emotional faces in middle-aged dizygotic twins at familial risk of depression - Miskowiak, K; Svendsen, A; Harmer, C; Reinecke, A; Elliott, R; Macoveanu, J; Siebner, H; Kessing, L; Vinberg, M (Cambridge University Press, 2017)
Background Negative bias and aberrant neural processing of emotional faces are trait-marks of depression but findings in healthy high-risk groups are conflicting. Methods Healthy middle-aged dizygotic twins (N = 42) underwent functional magnetic resonance imaging (fMRI): 22 twins had a co-twin history of depression (high-risk) and 20 were without co-twin history of depression (low-risk). During fMRI, participants viewed fearful and happy faces while performing a gender discrimination task. After the scan, they were given a faces dot-probe task, a facial expression recognition task and questionnaires assessing mood, personality traits and coping. Results Unexpectedly, high-risk twins showed reduced fear vigilance and lower recognition of fear and happiness relative to low-risk twins. During face processing in the scanner, high-risk twins displayed distinct negative functional coupling between the amygdala and ventral prefrontal cortex and pregenual anterior cingulate. This was accompanied by greater fear-specific fronto-temporal response and reduced fronto-occipital response to all emotional faces relative to baseline. The risk groups showed no differences in mood, subjective state or coping. Conclusions Less susceptibility to fearful faces and negative cortico-limbic coupling during emotional face processing may reflect neurocognitive compensatory mechanisms in middle-aged dizygotic twins who remain healthy despite their familial risk of depression.